2022
DOI: 10.1140/epjds/s13688-022-00343-9
|View full text |Cite
|
Sign up to set email alerts
|

Keyword expansion techniques for mining social movement data on social media

Abstract: Political and social scientists have been relying extensively on keywords such as hashtags to mine social movement data from social media sites, particularly Twitter. Yet, prior work demonstrates that unrepresentative keyword sets can lead to flawed research conclusions. Numerous keyword expansion methods have been proposed to increase the comprehensiveness of keywords, but systematic evaluations of these methods have been lacking. Our paper fills this gap. We evaluate five diverse keyword expansion techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…We also proved that the union of the expanded word lists does not yield to better results. These evidences are in contrast with the ones of [17], which are relative to the amount of relevant tweets key word expansion algorithms can retrieve. Indeed, the focus of the two papers is different as our analysis addresses a different research question and does not deal with the problem of text mining on Twitter.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We also proved that the union of the expanded word lists does not yield to better results. These evidences are in contrast with the ones of [17], which are relative to the amount of relevant tweets key word expansion algorithms can retrieve. Indeed, the focus of the two papers is different as our analysis addresses a different research question and does not deal with the problem of text mining on Twitter.…”
Section: Discussionmentioning
confidence: 75%
“…While informative, the work on Lexifield is based on a narrow set of methods (word embedding-based and knowledge-based approaches) and on a limited set of topics (sound, taste and odour). Another effort towards the creation of a baseline is constituted by [17]. There, the authors investigate the problem in relation to the retrieval of tweets.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high recall can benefit applications to a different range of problems, as for example in the area of text mining. In particular, Bozarth and Budak (2022) highlight that when considering the amount of relevant tweets that keyword expansion algorithms can retrieve, the union of expanded lexica leads to better results than the ones achieved by the single word lists.…”
Section: Discussionmentioning
confidence: 99%
“…While informative, the work on Lexifield is based on a narrow set of methods (word embedding-based and knowledge-based approaches) and on a limited set of topics (sound, taste, and odor). Another effort towards the creation of a baseline is constituted by Bozarth and Budak (2022). There, the authors investigate the problem in relation to the retrieval of tweets.…”
Section: Introductionmentioning
confidence: 99%
“…Another problem with DHS keywords is that they are non-lexical; therefore, exact matches result from bypassing meaningful or related words. As a result, pipelined keyword enhancing technique is implemented in [31] by integrating seed keywords with pipelines. In their work, the authors mentioned that the most relevant words with a particular topic are identified as seed keywords.…”
Section: Figure 1 Working Of Hash Function and Bitwise Function In Me...mentioning
confidence: 99%